Pengembangan Lembar Kerja Peserta Didik (LKPD) Bahasa Indonesia Kelas X Berbasis Think Talk Write Pada Materi Menulis Teks Biografi: Lembar Kerja Peserta Didik, Think Talk Write - Arozatulo Bawamenewi; Nesti Ratna Yanti Hulu (Ta'ehao: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2023)
Abstract This research was conducted to develop a Think Talk Write-based worksheet for writing biographical text. The researcher used the ADDIE development model as a guide in the implementation of development. To obtain the data for this study, the researcher used assessment instruments, namely validation questionnaire of a material expert, a linguist, a design expert, a student response questionnaire, and a learning outcome test. Data analysis was obtained by collecting quantitative and qualitative data from validators and students. The results of this study are that the value of the results of validation, trial and learning outcomes is found. Material expert validation in revision I reached 86.2% and in revision II reached 97.5%, linguist validation in revision I reached 82.1% and in revision II reached 100%, and design expert validation in revision I reached 75% and in revision II reached 100%, with very feasible criteria. Student responses to individual trials reached 98% and field trials reached 97%, with very practical criteria. Student learning outcomes in individual trials reached 100% and field trials reached 83.3%, with the criteria of Very Effective. The results of this study can be concluded, that is, that the development of Indonesian language worksheets for the 9th Grade Students of the SMA based on Think Talk Write is very feasible, very practical, and very effective to use in the Indonesian language learning process. Researchers suggest: 1) LKPD can be used by students and teachers in any school, 2) for teachers, it can be a reference in developing other creative teaching materials. Keywords: Learner Worksheet, Think Talk Write